Deuterium retention behavior of pure and Y2O3-doped tungsten investigated by nuclear reaction analysis and thermal desorption spectroscopy. (May 2018) - Zhao, M.; Jacob, W.; Gao, L.; Manhard, A.; Dürbeck, T.; Zhou, Z.
Highlights: Y2 O3 -doped W and pure W were exposed to D plasma at 370, 450 and 570 K. D retention was investigated by TDS and NRA. D inventory in Y2 O3 -doped tungsten higher than in pure tungsten. Presence of intrinsic defects with high trapping energies. Defects with high trapping energies are attributed to sub-micron pores present in the material. Abstract: Pure and Y2 O3 -doped tungsten samples were simultaneously exposed to deuterium (D) plasma. The following exposure parameters were investigated: ion energy of 38 eV/D, sample temperatures of 370, 450 and 570 K, and incident fluences of 6 × 10 24 and 7.5 × 10 25 D/m 2 . The deuterium retention behavior of these tungsten materials was investigated by nuclear reaction analysis and thermal desorption spectroscopy. After exposure at 450 K Y2 O3 -doped tungsten shows a D depth profile comparable with that of pure tungsten. But at each investigated exposure condition Y2 O3 -doped tungsten shows a higher total D inventory than pure tungsten. This is attributed to the presence of intrinsic defects with high trapping energies. Investigation of the D retention behavior of four different Y2 O3 -doped tungsten materials, which contain the same amount of Y2 O3, but have various microstructures, suggests that sub-micron pores are the underlying intrinsic defects responsible for the appearance of a high temperature D release peak.